Morphology and growth of maize: IITA research guide, No. 9 - Kling, J.; Edmeades, G.O. (1997)
Maize is one of the important food crops worldwide. It has a remarkable productive potential. However, considerable variation exists among varieties in morphology and growth habit. Management of a maize crop with respect to interaction of genotype and environment requires specific knowledge of maize growth and development.